QUALITY ASSESSMENT OF SMOKED SELAIS (Cryptopterus bicirrhis) RESULTS USING LABAN WOOD SMOKE WITH DIFFERENT METHODS FOR THE STORAGE ROOM TEMPERATURE - Suryanto, Ambrosius; Ilza, Mirna; ', Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted to determine the quality of smoked selais fish is stored at roomtemperature using different curing methods. five types of smoked selais fish were preserved usingliquid smoke from laban’s wood with treatment concentration of 6%, 8% which soaked in liquidsmoke rough, and concentration of 6%, 8% in the distillation of liquid smoke, immersion time 60and 90 minutes as the traditional fumigation control. Smoked selais fish were observed for 10, 20,30, 40 days. The results indicated that the smoked fish have a good and uniform quality of alltreatments, with the organoleptic quality assessment, water contain, pH, and peroxide.Keywords: Cryptopterus bicirchis, liquid smoked, laban wood